Should livestock images provide historical reference or modern reality? An examination of the Influence of Livestock Communication on Attitude. - Joy N Rumble; Tiffany M. Rogers-Randolph; Emily B. Buck (Journal of Applied Communications, 2019)
The livestock industry has repeatedly struggled to effectively communicate livestock care and handling practices in order to promote awareness and acceptance. Many consumers still hold on to the historically picturesque view of production agriculture instead of the modern reality. It is necessary for the industry to identify how much is too much to tell or show consumers. Therefore, this study sought to understand the influence of two communication treatments on attitudes toward livestock care and use. Elaboration Likelihood Model (ELM) served as the theoretical framework for this study. A sample of 1,049 respondents was obtained through non-probability sampling. To fulfill the purpose of this study, the development of an online survey was informed by ELM and measured prior beliefs, personal involvement, and knowledge. An experimental treatment, consistent with persuasive communication within ELM, presented respondents with one of two images of cage-free egg laying housing and accompanying text. One image could be described as “historically picturesque” and the other as “modern reality.” Attitude toward livestock care and use was measured after exposure to one of the images. Respondents held favorable prior beliefs, demonstrated neutral involvement, and answered three or less knowledge questions correctly. Respondents exposed to the modern reality treatment displayed slightly lower attitudes than those exposed to the historically picturesque treatment. The results indicated that both prior beliefs and image exposure had a significant impact on attitude, while personal involvement was not found to be significant.
Keywords: Elaboration Likelihood Model; Livestock care and use; persuasion